Exploring the role of perceived risk and habit in safe food-handling behaviour change. (April 2022) - Charlesworth, Jessica; Mullan, Barbara; Howell, Joel; Tan, Henry; Abbott, Bree; Potter, Abbey
Abstract: The incidence of food poisoning remains high in Australia, particularly in Queensland and Western Australia. A recent safe food-handling media campaign was piloted in Busselton, Western Australia, and was found to lead to improvements in half of the safe food-handling behaviours targeted; however, safe food-handling knowledge did not increase. Consequently, the mechanisms underlying this behaviour change remain unknown. Therefore, the aim of the present study was to determine the mechanisms of behaviour change observed as a result of the pilot safe food-handling media campaign. Data from 117 participants who indicated whether or not they recalled the media campaign advertisements were analysed. Measures of perceived risk related to safe food-handling, safe food-handling habit, and safe food-handling behaviour were collected prior to and following the pilot safe food-handling media campaign. Mediation analyses were conducted to determine if the media campaign advertisements predicted change in behaviour via change in perceived risk and habit. Results indicated that perceived risk and habit play an important role in safe food-handling behaviour change. These findings have implications for content development of future public health messages related to safe food-handling. Highlights: Change in perceived risk and habit directly predicted change in all behaviours. Media campaign recall directly predicted change in habit for one behaviour. Media campaign recall did not directly predict change in perceived risk. Media campaign recall did not directly predict change in behaviour. No mediation effects were found for change in perceived risk and habit.